High dielectric composite material and preparation method thereof
Through polymer blending technology and the addition of graphene nanoparticles, combined with ethanol treatment and hot pressing forming methods, the problem of difficult to take into account the processing performance and dielectric properties of existing high dielectric materials is solved, and the industrial application of high dielectric composite materials is realized.
Patent Information
- Application Number
- CN202311398343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing high-dielectric materials are difficult to take into account both processing performance and dielectric properties, and the preparation method is complex, which is not conducive to industrial application.
Through polymer blending technology, a high dielectric composite material is prepared by combining polystyrene, ethylene octene block polymer and graphene nanoparticles, and the processing is carried out by ethanol mixing, filtration, cleaning, drying and hot pressing molding.
The advantages of each component are complementary, the physical and mechanical properties and processing properties of the material are improved, the cost is reduced, the scope of use is expanded, and the dielectric constant is significantly improved and the dielectric loss is reduced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a high dielectric composite material and a preparation method thereof. Background Art
[0002] High dielectric materials are widely used in communication technology, power engineering, science and technology, etc. High dielectric materials can generally be divided into polymer materials and inorganic materials. Inorganic materials have high dielectric constants, but large dielectric losses, low dielectric strength, and poor processing performance; polymer materials have high dielectric strength, good flexibility, and easy processing, but low dielectric constants. Adding inorganic high dielectric materials or conductive materials to polymer materials can effectively improve the dielectric properties of polymer materials.
[0003] The prior art method for preparing conductive polymer composite materials has relatively strict requirements on experimental operations, and requires precise control of the formulation of the blend, the processing method and the addition of the compatibilizer, so as to carefully control the morphology and properties of the blend, which is not conducive to industrialization. Summary of the invention
[0004] In order to solve the above problems in the prior art, the present invention provides a high dielectric composite material and a preparation method thereof.
[0005] In a first aspect, the present invention provides a high dielectric composite material, the components of which include polystyrene, ethylene octene block polymer, and graphene nanoparticles.
[0006] It should be noted that polystyrene is a thermoplastic polymer with good mechanical properties and good processability and has a wide range of industrial applications. However, the brittleness of polystyrene limits its application in some fields. Ethylene octene copolymer (EOC) is a new type of polyolefin elastomer. In recent years, it has been used to enhance the ductility of thermoplastic resins due to its good processability and high impact resistance. Since polystyrene and ethylene octene copolymer are difficult to miscible, other components need to be added to improve the compatibility of the two. Graphene has a unique structure and a high aspect ratio. It is easier to form a 3D network structure when the content is low, so that the material has conductivity and good mechanical properties. At the same time, it has excellent optical, electrical, and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery. It is considered to be a revolutionary material in the future. By means of polymer blending, polystyrene, ethylene octene block polymer and graphene nanoparticles are mixed to obtain composite materials. This can achieve complementary advantages of each component, improve the physical and mechanical properties and processing properties of the polymer, reduce costs and expand the scope of application. This is also one of the important ways to achieve polymer modification and produce new materials with multiple properties.
[0007] As a specific embodiment of the present invention, the mass ratio of the polystyrene, ethylene octene block polymer, and graphene nanoparticles is (75-85): (15-25): (0.5-1.5), preferably 80:20: (0.5-1.5);
[0008] As a specific embodiment of the present invention, the polystyrene melt flow index is 11-12 g / 10 min (200° C. / 5 kg), and the styrene monomer content is less than 500 ppm.
[0009] As a specific embodiment of the present invention, the ethylene octene block polymer has a melt flow index of 4.5 to 5.5 g / 10 min (190° C. / 2.16 kg), and a 1-octene unit content of 20 to 40 wt.%.
[0010] As a specific embodiment of the present invention, the graphene nanoparticles have a thickness of 10 to 100 nm and a diameter of 1 to 3 μm.
[0011] As a specific embodiment of the present invention, the dielectric constant of the high dielectric composite material at 10 MHz is 3 to 56, and the dielectric loss is less than 0.02.
[0012] In a second aspect, the present invention provides a method for preparing a high dielectric composite material, which is characterized by comprising: mixing a mixed solution containing polystyrene, ethylene octene block polymer, and graphene nanoparticles with ethanol, filtering, washing, drying, and hot pressing to obtain the mixed solution.
[0013] As a specific embodiment of the present invention, the ethanol temperature is -2 to 2°C.
[0014] As a specific embodiment of the present invention, the cleaning is repeated with ethanol, and the drying temperature is 100-120°C; the hot pressing molding conditions include: heating temperature to 180-220°C, and pressure of 12-20MPa.
[0015] It should be noted that the mixture containing polystyrene, ethylene octene block polymer and graphene nanoparticles has low solubility in ethanol and can precipitate, so the solvent of the mixture is N,N-dimethylformamide. N,N-dimethylformamide can be removed by washing with ethanol and filtering.
[0016] As a specific embodiment of the present invention, the preparation method of the graphene nanoparticles is as follows: immersing graphite foil in an electrolyte, using platinum as a cathode, first applying a preset voltage, and then applying a main voltage until the graphene is completely peeled off; washing, vacuum filtering, and drying the obtained graphene powder to obtain graphene nanoparticles.
[0017] As a specific embodiment of the present invention, the electrolyte is nitric acid, ammonium sulfate or sodium dodecyl sulfate solution with a concentration of 0.2 mol / L.
[0018] As a specific embodiment of the present invention, the conditions for applying voltage include: a preset voltage of 5 to 8 V, a preset voltage application time of 3 to 8 minutes, a main voltage of 8 to 12 V, and a main voltage application time of 6 to 8 hours.
[0019] As a specific implementation of the present invention, the rinsing is repeated with deionized water; the drying temperature is 40-60°C.
[0020] As a specific embodiment of the present invention, the method for preparing the mixed solution containing polystyrene, ethylene octene block polymer and graphene nanoparticles comprises the following steps:
[0021] S1: adding graphene nanoparticles to N,N-dimethylformamide and mixing them evenly to obtain a graphene dispersion;
[0022] S2: adding polystyrene and ethylene octene block polymer into toluene and mixing evenly to obtain a polymer solution;
[0023] S3: The graphene dispersion obtained in step S1 and the polymer solution obtained in step S2 are mixed evenly to obtain a mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles.
[0024] As a specific embodiment of the present invention, in step S1, the volume of N,N-dimethylformamide is 8 to 12 mL; the thickness of the graphene nanoparticles is 10 to 100 nm, and the diameter is 1 to 3 μm; the mass of the graphene nanoparticles is 0.04 to 0.12 g; and the uniform mixing includes using an ultrasonic bath to make them uniformly dispersed.
[0025] As a specific embodiment of the present invention, in the step S2, the mass ratio of the polystyrene to the ethylene octene block polymer is (3-5):1, preferably, the mass ratio is 4:1.
[0026] As a specific embodiment of the present invention, in the step S2, the purity of the toluene solution is 99%, and the volume is 70-90 mL; the mass of the polystyrene and ethylene octene block polymer is 7-9 g.
[0027] As a specific embodiment of the present invention, in the step S2, the uniform mixing includes: heating to a temperature of 80 to 90° C. and a stirring rate of 1000 to 2000 rpm.
[0028] The above raw materials in the present invention can be prepared in-house or commercially available, and the present invention is not particularly limited thereto.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The high dielectric composite material of the present invention is obtained by mixing polystyrene, ethylene octene block polymer and graphene nanoparticles through polymer blending, filtering, washing, drying and hot pressing, so as to achieve complementary advantages of each component, improve the physical and mechanical properties and processing performance of the polymer, reduce costs and expand the scope of application.
[0031] 2. The dielectric constant of the dielectric composite material of the present invention is increased by about 25 times compared with styrene / ethylene octene block polymer.
[0032] 3. The technical solution adopted by the present invention is simple to operate, and the prepared material has the advantages of good dielectric properties and good flexibility. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0034] The specific information of the reagents used in the embodiments of the present invention is as follows:
[0035] Polystyrene, melt flow index is 10g / 10min (200℃ / 5kg), manufacturer is Total, France, brand GPPS1540;
[0036] Ethylene octene block polymer, melt flow index is 5g / 10min (190℃ / 2.16kg), 1-octene unit content is 30wt.%.
[0037] Example 1
[0038] This embodiment provides a high dielectric composite material and a preparation method thereof, the specific details of which are as follows:
[0039] S1: Preparation of graphene nanoparticles;
[0040] A graphite foil with a length of 1 cm and a width of 5 cm was immersed in 75 mL of a 0.2 mol / L nitric acid electrolytic solution. Platinum was used as the cathode. A 5 V preset voltage was first applied for 5 minutes, and then an 8 V main voltage was applied until the graphene was completely peeled off. The obtained graphene powder was repeatedly rinsed with deionized water, vacuum filtered, and finally dried at 50°C to obtain graphene nanoparticles; the thickness was ~50 nm and the diameter was ~2 μm.
[0041] S2: preparing a mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles;
[0042] 0.0075 g of graphene particles were added to 10 mL of N,N-dimethylformamide, and the particles were evenly dispersed in an ultrasonic bath to obtain a graphene dispersion;
[0043] 0.4 g of polystyrene and 0.1 g of ethylene octene block polymer were added to 80 mL of toluene and stirred at 90° C. for about half an hour to obtain a uniform polymer solution.
[0044] The graphene dispersion and the polymer solution are ultrasonically mixed to obtain a mixed solution containing polystyrene, ethylene octene block polymer and graphene nanoparticles.
[0045] S3: Preparation of polystyrene / ethylene octene block polymer / graphene composites
[0046] A mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles was added into 1L of low-temperature ethanol, and the precipitate was repeatedly washed with ethanol, dried at 110°C, and then hot-pressed at 200°C with a pressure of 15MPa.
[0047] In the polystyrene / ethylene octene block polymer / graphene composite material obtained in Example 1, polystyrene accounts for 78.8%, ethylene octene block polymer accounts for 19.7%, and graphene nanoparticles account for 1.5%;
[0048] At a frequency of 10 MHz, the dielectric constant of the obtained polystyrene / ethylene octene block polymer / graphene composite material was measured to be 55.8, and the dielectric loss was 0.007; at an angular frequency of 100 rad / s, the dynamic mechanical thermal analysis test obtained a storage modulus of about 1×10 5 Pa, complex viscosity is 4.0×10 3 Pa.s.
[0049] Example 2
[0050] This embodiment provides a high dielectric composite material and a preparation method thereof, the specific details of which are as follows:
[0051] S1: Preparation of graphene nanoparticles
[0052] A 1cm long and 5cm wide graphite foil was immersed in 75mL 0.2mol / L ammonium sulfate electrolytic solution, with platinum as the cathode, and a preset voltage was applied for 5 minutes, and then the main voltage was applied until the graphene was completely peeled off. The obtained graphene powder was repeatedly rinsed with deionized water, vacuum filtered, and finally dried at 50°C; its thickness was ~30nm and its diameter was ~1μm.
[0053] S2: Preparation of polystyrene, ethylene octene block polymer, and graphene nanoparticles mixed solution
[0054] 0.0075 g of graphene particles were added to 10 mL of N,N-dimethylformamide, and the particles were evenly dispersed in an ultrasonic bath to obtain a graphene dispersion.
[0055] 6.4 g of polystyrene and 1.6 g of ethylene octene block polymer were added to 80 mL of toluene solution and stirred at 90° C. for about half an hour to obtain a uniform polymer solution. The graphene dispersion and the polymer solution were ultrasonically mixed to obtain a mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles.
[0056] S3: Preparation of polystyrene / ethylene octene block polymer / graphene composites
[0057] A mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles was added into 1L of low-temperature ethanol, and the precipitate was repeatedly washed with ethanol, dried at 110°C, and then hot-pressed at 200°C with a pressure of 15MPa.
[0058] The polystyrene / ethylene octene block polymer / graphene composite material obtained in Example 2 has a dielectric constant of 7 and a dielectric loss of 0.02 at a frequency of 10 MHz. When the angular frequency is 100 rad / s, the storage modulus obtained by dynamic mechanical thermal analysis is about 1×10 5 Pa, complex viscosity is 4.0×10 3 Pa.s.
[0059] Example 3
[0060] This embodiment provides a high dielectric composite material and a preparation method thereof, the specific details of which are as follows:
[0061] S1: Preparation of graphene nanoparticles
[0062] A graphite foil with a length of 1 cm and a width of 5 cm was immersed in 75 mL of 0.2 mol / L sodium dodecyl sulfate electrolytic solution, with platinum as the cathode, and a preset voltage was applied for 5 minutes, and then the main voltage was applied until the graphene was completely peeled off. The obtained graphene powder was repeatedly rinsed with deionized water, vacuum filtered, and finally dried at 50°C; its thickness was ~60 nm and its diameter was ~3 μm
[0063] S2: Preparation of polystyrene, ethylene octene block polymer, and graphene nanoparticles mixed solution
[0064] 0.0075 g of graphene nanoparticles were added to 10 mL of N,N-dimethylformamide solution, and the mixture was dispersed evenly in an ultrasonic bath to obtain a graphene dispersion. 6.4 g of polystyrene and 1.6 g of ethylene octene block polymer were added to 80 mL of toluene solution, and stirred at 90°C for about half an hour to obtain a uniform polymer solution. The graphene dispersion and the polymer solution were ultrasonically mixed to obtain a mixed solution of polystyrene, ethylene octene block polymer, and graphene nanoparticles.
[0065] S3: Preparation of polystyrene / ethylene octene block polymer / graphene composites
[0066] A mixed solution of polystyrene, ethylene octene block polymer and graphene nanoparticles was added into 1L of low-temperature ethanol, and the precipitate was repeatedly washed with ethanol, dried at 110°C, and then hot-pressed at 200°C with a pressure of 15MPa.
[0067] The polystyrene / ethylene octene block polymer / graphene composite material obtained in Example 3 has a dielectric constant of 4 and a dielectric loss of 0.0275 at a frequency of 10 MHz. When the angular frequency is 100 rad / s, the dynamic mechanical thermal analysis test shows that its storage modulus is about 4.0×10 4 Pa, complex viscosity is 1.0×10 3 Pa.s.
[0068] Comparative Example 1
[0069] This comparative example does not contain graphene, but only contains polystyrene and ethylene octene block polymer, and the specific details are as follows:
[0070] S1: Preparation of polystyrene and ethylene octene block polymers
[0071] 6.4 g of polystyrene and 1.6 g of ethylene octene block polymer were added to 80 mL of toluene solution and stirred at 90° C. for about half an hour to obtain a uniform polymer mixture.
[0072] S3: Preparation of polystyrene / ethylene octene block polymer composites
[0073] The mixed liquid of polystyrene and ethylene octene block polymer is added into 1L of ethanol at a temperature of -2 to 2°C, the precipitate is repeatedly washed with ethanol, dried at 110°C, and then hot-pressed at 200°C with a pressure of 15MPa.
[0074] At a frequency of 10 MHz, the dielectric constant of the obtained polystyrene / ethylene octene block polymer composite material was measured to be 2, and the dielectric loss was 2.5×10 -5 When the angular frequency is 100 rad / s, the storage modulus obtained by dynamic mechanical thermal analysis is about 2.0×10 4Pa, complex viscosity is 2.5×10 2 Pa.s. This shows that the addition of graphene can improve the dielectric properties of the composite material.
[0075] Comparative Example 2
[0076] In step S2 of Example 1, 0.0025 g of graphene nanoparticles were added, and the rest was the same as in the example.
[0077] At a frequency of 10 MHz, the dielectric constant of the obtained polystyrene / ethylene octene block polymer composite material was measured to be 3, and the dielectric loss was 3×10 -3 . This indicates that as the graphene content increases, the dielectric properties of the composite material improve.
[0078] Comparative Example 3
[0079] In step S2 of Example 2, 0.0025 g of graphene nanoparticles are added, and the rest is the same as Example 2.
[0080] At a frequency of 10 MHz, the dielectric constant of the obtained polystyrene / ethylene octene block polymer composite material was measured to be 3.2 and the dielectric loss was 6×10 -3 . This indicates that as the graphene content increases, the dielectric properties of the composite material improve.
[0081] Comparative Example 4
[0082] In step S2 of Example 3, 0.0025 g of graphene nanoparticles are added, and the rest is the same as in the example.
[0083] At a frequency of 10 MHz, the dielectric constant of the obtained polystyrene / ethylene octene block polymer composite material was measured to be 4, and the dielectric loss was 2.75×10 -2 . This indicates that as the graphene content increases, the dielectric properties of the composite material improve.
[0084] In summary, the high dielectric composite material of the present invention is obtained by mixing polystyrene, ethylene octene block polymer, and graphene nanoparticles, filtering, washing, drying, and hot pressing to obtain a composite material by polymer blending, which can achieve complementary advantages of each component, improve the physical and mechanical properties and processing properties of the polymer, reduce costs, and expand the scope of use. The dielectric constant of the dielectric composite material prepared in the embodiment is increased by about 25 times compared with that of styrene / ethylene octene block polymer.
[0085] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0086] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A high dielectric composite material, characterized in that: Including polystyrene, ethylene octene block polymer, and graphene nanoparticles.
2. The high dielectric composite material according to claim 1, characterized in that: The mass ratio of the polystyrene, ethylene octene block polymer and graphene nanoparticles is (75-85): (15-25): (0.5-1.5), preferably 80:20: (0.5-1.5); The polystyrene melt flow index is 11-12 g / 10 min (200° C. / 5 kg), and the styrene monomer content is less than 500 ppm; The ethylene octene block polymer has a melt flow index of 4.5 to 5.5 g / 10 min (190° C. / 2.16 kg) and a 1-octene unit content of 20 to 40 wt.%; The graphene nanoparticles have a thickness of 10 to 100 nm and a diameter of 1 to 3 μm.
3. The high dielectric composite material according to claim 1 or 2, characterized in that: The high dielectric composite material has a dielectric constant of 3 to 56 at 10 MHz and a dielectric loss of less than 0.
02.
4. A method for preparing the high dielectric composite material according to any one of claims 1 to 3, characterized in that: include: The mixed liquid containing polystyrene, ethylene octene block polymer and graphene nanoparticles is mixed with ethanol, filtered, washed, dried and hot-pressed to obtain the mixed liquid.
5. The preparation method according to claim 4, characterized in that: The ethanol temperature is -2 to 2°C; And / or, the cleaning is carried out by ethanol cleaning, and / or, the drying temperature is 100-120°C; and / or, the hot pressing molding conditions include: heating temperature to 180-220°C and pressure of 12-20MPa.
6. The preparation method according to claim 4 or 5, characterized in that: The preparation method of the graphene nanoparticles comprises the following steps: immersing a graphite foil in an electrolyte, using platinum as a cathode, first applying a preset voltage, and then applying a main voltage until the graphene is completely peeled off; washing, vacuum filtering, and drying the obtained graphene powder to obtain graphene nanoparticles.
7. The preparation method according to claim 6, characterized in that: The electrolyte is nitric acid, ammonium sulfate or sodium dodecyl sulfate solution with a concentration of 0.2 mol / L; And / or, the conditions for applying voltage include: the preset voltage is 5 to 8V, the preset voltage is applied for 3 to 8 minutes, the main voltage is 8 to 12V, and the main voltage is applied for 6 to 8 hours; And / or, the rinsing is performed with deionized water; and / or, the drying temperature is 40-60°C.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method of the mixed solution containing polystyrene, ethylene octene block polymer and graphene nanoparticles comprises the following steps: S1: adding graphene nanoparticles to N,N-dimethylformamide and mixing them evenly to obtain a graphene dispersion; S2: adding polystyrene and ethylene octene block polymer into toluene and mixing evenly to obtain a polymer solution; S3: The graphene dispersion obtained in step S1 and the polymer solution obtained in step S2 are mixed evenly to obtain a mixed solution containing polystyrene, ethylene octene block polymer and graphene nanoparticles.
9. The preparation method according to claim 8, characterized in that: In the step S1, the volume of N,N-dimethylformamide is 8 to 12 mL; And / or, the graphene nanoparticles have a thickness of 10 to 100 nm and a diameter of 1 to 3 μm; And / or, the mass of the graphene is 0.04 to 0.12 g; And / or, the uniform mixing includes using an ultrasonic bath to achieve uniform dispersion.
10. The preparation method according to claim 8, characterized in that: In the step S2, the mass ratio of the polystyrene to the ethylene octene block polymer is (3-5):1, preferably, the mass ratio is 4:1; And / or, the purity of the toluene is 99%, and the volume is 70-90 mL; the mass of the polystyrene and ethylene octene block polymer is 7-9 g; And / or, the uniform mixing includes: heating to a temperature of 80-90° C. and a stirring rate of 1000-2000 rpm.